IMPLEMENTASI PERAN GURU DALAM MENINGKATKAN MUTU MANAJEMEN SEKOLAH DI SD MUHAMMADIYAH BOARDING SCHOOL PRAMBANAN - Fitriana, Anisha Eka; Saifudin, Muhamad Fakhrur (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
This study aims to describe the form of teacher activity and describe the implementation of the teacher's role in improving the quality of school management. The subjects of this study were the school principal, teachers, and students at SD Muhammadiyah Boarding School Prambanan. Data collection methods using interview, observation, and documentation techniques. Data analysis techniques using interactive technologies. The data validity used methodological triangulation and source triangulation. The results showed that the role of teachers in improving the quality of school management includes the role as a source of learning there is mastery of the material, as a teacher facilitator using the media, as a manager by creating optimal learning conditions, as a demonstrator by giving suitable examples to students, as a guide by recognizing the abilities and potential of students, as a motivator by providing motivation, as an evaluator by providing an evaluation. Every morning, elementary school teachers from Muhammadiyah Boarding School motivate character-building programs. Each class has its target to shape the character of students through daily habituation that did with the teacher.